2000
DOI: 10.1021/jo991947q
|View full text |Cite
|
Sign up to set email alerts
|

Manganese(III) Acetate Initiated Oxidative Free Radical Reactions between 2-Amino-1,4-naphthoquinones and β-Dicarbonyl Compounds

Abstract: Free radical reactions have become increasingly important in organic synthesis in the last two decades. 1 Compounds containing the quinone group represent an important class of biologically active molecules that are widespread in nature. 2,3 Electrophilic radicals produced from the manganese(III) acetate oxidation of β-dicarbonyl compounds undergo efficient addition to a C-C double bond. 1d,e,4,5 These reactions can be performed intermo-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Jiang and Chuang indicated that upon treatment of 2‐(ethylamino)‐1,4‐naphthoquinone ( 66d ) with 2,4‐pentanedione and manganese (III)acetate under similar conditions, compound 76a was obtained in 65% yield and other by‐cyclized products 77 and 78 (Scheme ) [56]. Oxidation of the β‐keto ester by manganese (III) acetate gives radical 79 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Jiang and Chuang indicated that upon treatment of 2‐(ethylamino)‐1,4‐naphthoquinone ( 66d ) with 2,4‐pentanedione and manganese (III)acetate under similar conditions, compound 76a was obtained in 65% yield and other by‐cyclized products 77 and 78 (Scheme ) [56]. Oxidation of the β‐keto ester by manganese (III) acetate gives radical 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of the β‐keto ester by manganese (III) acetate gives radical 79 . Addition of the radical intermediate to the quinone ring, followed by oxidation, gives 80 (Scheme ) [56]. Compound 80 underwent condensation to produce 76a (path a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations